Constraining late paleozoic ice extent in the Paganzo basin of western Argentina: Provenance of the lower Paganzo group strata. (March 2021) - Pauls, Kathryn N.; Isbell, John L.; Limarino, C. Oscar; Alonso-Murauga, Pablo J.; Malone, David H.; Schencman, L. Jazmin; Colombi, Carina E.; Moxness, Levi D.
Abstract: The western margin of Gondwana records evidence of mid-Carboniferous glaciation (Visean- Bashkirian) in the strata of the Paganzo Basin and adjacent areas. Previous studies focused on constraining the orientations of ice flow and generalizing the extent and occurrence of glacial ice in the basin. However, there is uncertainty occurs concerning the location and extent of glaciation and the locations of glacial centers during deposition of the Guandacol Formation located in the western portion and the time correlative Malanzán Formation in the eastern parts of the basin respectively. Understanding these strata and the conditions that led to the deposition of these strata has important implications for understanding glaciation extent along the western margin of Gondwana during the late Paleozoic ice age. To refine the glaciation history, we present new paleocurrent, facies, and a comparative analysis of previously published and one new detrital zircon geochronology data set. Together, these data provide new insight into sediment dispersal patterns and glacial centers within the basin. Our data indicate that both units were deposited under cold climatic conditions that occurred across the entire basin, but that glaciers were restricted to the western portion of the basin. The facies analysis for both formations indicates very different depositional environments for the two units: glacial and glaciomarine environments in the west and non-glacial alluvial, alluvial fan and lacustrine and/or marine environments in the east. Detrital zircon geochronology indicates separate localized provenance signatures for the two formations. Furthermore, the detrital zircon populations allude to disconnected depositional centers. At Huaco, glacial flow in the Guandacol is oriented toward the northwest (i.e. 313°) and appears to be draining from an uplift that contains similar zircon age populations as the Sierra de Valle Fértil and Sierra de Pie de Palo ranges. In the Olta-Malanzán paleovalley system, drainage was off valley walls and down the valley axis (i.e. south and southwest) within the Sierras de Chepes region with limited sediment sourced from the east just beyond the paleovalley system. Paleoflow measurements reported from other known glacial localities along the western portion of the basin reflect a radial flow pattern within and away from deeply incised valleys that clearly point to upland glacial centers within the Cuyania and Precordilleran terranes. Highlights: Detrital zircon populations and new paleoflow data show there were multiple depositional centers in the mid-Carboniferous Paganzo Basin. The Guandacol Formation at Huaco represents a depocenter of sediment from the Sierra de Pie de Palo or Sierra Valle Fértil. The Malanzán Formation sediments are sourced from the Sierra de Chepes region, with minor influence from Sierra de Córdoba. Paleoflow data reveal glaciated uplands along the Protoprecordillera range, while the eastern Paganzo Basin was unglaciated.